Towards an objective comparison of feature extraction techniques for automatic speaker recognition systems - Ayoub Bouziane; Jamal Kharroubi; Arsalane Zarghili (Institute of Advanced Engineering and Science, 2021)
A common limitation of the previous comparative studies on speaker-features extraction techniques lies in the fact that the comparison is done independently of the used speaker modeling technique and its parameters. The aim of the present paper is twofold. Firstly, it aims to review the most significant advancements in feature extraction techniques used for automatic speaker recognition. Secondly, it seeks to evaluate and compare the currently dominant ones using an objective comparison methodology that overcomes the various limitations and drawbacks of the previous comparative studies. The results of the carried out experiments underlines the importance of the proposed comparison methodology.